Migration and the Transition to Adulthood in Contemporary Malawi - Beegle, Kathleen; Poulin, Michelle (World Bank, Washington, DC, 2013)
In many African countries, the timing of important life events -- such as school-leaving, first marriage, and entry into the labor market -- is thought to be strongly tied to migration. This paper investigates the relationship between major life events, household characteristics, and migration among adolescents and young adults in contemporary Malawi. The specific research questions are twofold. First, what are the socio-economic and demographic determinants of migration? Second, how do school attendance, first marriage, and employment-seeking relate to migration patterns? The study uses panel data collected from a survey designed specifically to explore socioeconomic and demographic aspects of youth transitions to adulthood and which tracked respondents as they moved to new dwellings. Among the sample, they find that moves are not uncommon, and the predominant reasons for moves are non-economic. Although historically ethnic traditions in this area have held that girls and women usually did not move upon marrying, the data show that women were more likely to move between survey rounds than boys and men, and that marriage was the main reason for doing so. Closer ties to the head of the household are associated with less movement for both women and men.